1999
DOI: 10.1038/sj.jim.2900698
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture conditions on production and freeze-drying tolerance of Paecilomyces fumosoroseus blastospores

Abstract: With the goal of developing a defined medium for the production of desiccation-tolerant blastospores of the bioinsecticidal fungus Paecilomyces fumosoroseus, we evaluated the impact of various media components such as amino acids, carbohydrates, trace metals and vitamins on hyphal growth and sporulation of P. fumosoroseus cultures and on the freeze-drying tolerance of blastospores produced under these conditions. A comparison of 13 amino acids as sole nitrogen sources showed that glutamate, aspartate, glycine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 23 publications
1
21
0
1
Order By: Relevance
“…Since Zn 2+ was signed as one of the most important cations for the growth of I. fumosorosea [23] and in an earlier publication was established that a range of 10-100 M Zn 2+ was optimal for biomass production [24], a concentration of 20 mg/l of ZnSO 4 ·7H 2 O (70 M Zn 2+ ) was assumed as adequate.…”
Section: Resultsmentioning
confidence: 99%
“…Since Zn 2+ was signed as one of the most important cations for the growth of I. fumosorosea [23] and in an earlier publication was established that a range of 10-100 M Zn 2+ was optimal for biomass production [24], a concentration of 20 mg/l of ZnSO 4 ·7H 2 O (70 M Zn 2+ ) was assumed as adequate.…”
Section: Resultsmentioning
confidence: 99%
“…(formerly Paecilomyces farinosus) (Hypocreales: Cordycipitaceae) aiming to control several insect pests, due to the capacity these entomopathogens have to cause natural epizootics (Zimmermann, 2008). The capacity to grow and produce conidia in many carbon and nitrogen sources is one of the factors that make an inexpensive mass production of these fungi possible (Cliquet and Jackson, 1999). Isaria fumosorosea and Lecanicillium spp.…”
Section: Introductionmentioning
confidence: 99%
“…While carbohydrates like glucose appear to enhance the desiccation tolerance of blastospores during freeze-drying [3], storage stability is unaffected.…”
Section: Discussionmentioning
confidence: 95%
“…Blastospore survival was restored when these blastospores were suspended in 2.5% glucose solution prior to freeze-drying, as previously described [3]. Other studies have also shown that the presence of glucose in the supernatant stabilized fungal cells during desiccation [2,24].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation